Soft and Hard Skills to Be Developed By a Pre-Service Teacher under Distance Learning: Case Study (International Journal of Scientific Research and Management (IJSRM), 2024)
This article reflects on the development of soft and hard skills and their importance within the academic and educational course of students who study a degree in English as a foreign language under the distance modality. At the center of this study, the opinions of 46 students from various semesters underscore the fundamental role that the cultivation of these competencies plays in distance education. The qualitative approach and NVIVO software were used in a multiple case study to carry out axial coding. In this way, the information was classified into 6 categories, supported by the opinions provided by the survey participants: Personal Growth, Assertive Communication, Professional Enrichment, Digital Management, Pedagogical Confrontation, and English Proficiency. By analyzing the perspectives of these students, the research concludes that pre-service teachers have a valuable perspective on the development of competencies and recognize the integration of these competencies in their distance learning path, promoting personal and professional growth for their future roles.